TRAINING ON MAKING THE NUTRITIOUS ANIMAL FEED FROM RICE STRAW THROUGH FERMENTATION FOR THE SOCIETY OF NISAM DISTRICT - Hassan, Soraya Masthura; Aiyub, Hendra; Husna, Asmaul; Bahri, Samsul; M Nur, Rizki Alamsyah Dafa (Universitas Muhammadiyah Aceh, 2022)
Animal feed is food given to the pets. Animal feed is very important thing in aquaculture activities in the livestock sector. Rice straw is the main choice for livestock feed. The content of the nutrition in the rice straw are 4.60% crude protein and 28.86% crude fiber, thats not good for livestock growth and caused the farmers economic condition. Even though the rice field land in Nisam sub-dictrict is quite wide and there is a lot of rice waste during the harvest season, but the people still not optimized its utilization. Optimizing the utilization of damaged rice straw can support the need for high nutrition content in animal feed, so that the livestock can grow well. To improve the quality of rice straw, it is necessary to carry out the process in using the probiotics then it is easily digested by livestock. This condition will improve the welfare of the breeders. Therefore, the community empowerment activities are carried out by making animal feed from rice straw waste that is wept in Nisam sub-district, North Aceh RegencyKey words: Empowerment, animal feed, rice straw waste, fermentation